Comparison of different solvent types for determination biological activities of myrtle berries collected from Turkey - Polat, B.; Oba, S.; Karaman, K.; Arici, M.; Sagdic, O. (WAGENINGEN ACADEMIC PUBLISHERS, 2014)
In the present study, we investigated the effects of four extracting solvents (70% acetone:water (v/v), 80% ethanol:water (v/v), 80% methanol:water (v/v) and distilled water) on the total phenolic content and antiradical, antioxidant activity and antimicrobial activities of extracts of myrtle berries (Myrtus communis) collected from eight different locations in Turkey. The tested plant extracts were found to contain appreciable amounts of total phenolic contents (39.933 to 207.4 mg GAE/g dry extract) and have 1.1-diphenyl-2- picrylhydrazyl scavenging activity ranging between 6.73 and 65.6%. The antioxidant activity of the myrtle fruits was measured using the phosphomolybdenum spectrophotometric method. The highest antioxidant activity value (241.533 mg ascorbic acid equivalents /g dry extract) was observed in the methanolic extract of the fifth sample. The agar diffusion method was used to determine the antimicrobial activity of the extract samples. It was found that the methanol and acetone extracts were more efficient against six pathogenic bacteria including Bacillus cereus, Escherichia coli O157:H7, Listeria monocytogenes, Staphylococcus aureus, Salmonella Typhimurium and Yersinia enterocolitica. The solvent systems used for extraction had an important effect on the bioactive compounds extracted. Based on the results, we conclude that myrtle berries can be considered as a good source of natural antioxidant and natural antimicrobial compounds.
Keywords: antimicrobial activity; antioxidant activity; myrtle berry; solvent type; total phenolic content; FATTY-ACID-COMPOSITION; COMMUNIS L.; ESSENTIAL OILS; IN-VITRO; FRUITS; WILD; POLYPHENOLS; EXTRACTS; Food Science & Technology